Assessing serum metabolite profiles as predictors for feed efficiency in broiler chickens reared at geographically distant locations. Issue 6 (2nd November 2017) - Metzler-Zebeli, B. U.; Magowan, E.; Hollmann, M.; Ball, M. E. E.; Molnár, A.; Lawlor, P. G.; Hawken, R. J.; O'Connell, N. E.; Zebeli, Q.
ABSTRACT: 1. The objective of this study was to investigate differences in growth performance, serum intermediary metabolites, acute-phase proteins and white blood cells in low, medium and high–residual feed intake (RFI) chickens. It was also assessed if the environment affects the feed efficiency (FE) and FE-related performance and serum profiles of chickens. 2. Individual body weight (BW) and feed intake (FI) were recorded from d 7 of life. At 5 weeks of age, female and male broiler chickens (Cobb 500) were selected according to their RFI (L1: Austria; L2: UK; n = 9/RFI group, sex and locatity -45on) and blood samples were collected. 3. Chickens at L1 had similar FI but a 15% higher BW gain compared to chickens at L2. The RFI values of female chickens were −231, 8 and 215 g and those of male chickens −197, 0 and 267 g for low, medium and high RFI, respectively. 4. Location affected serum glucose, urea, cholesterol, non-esterified fatty acids (NEFA) and ovotransferrin in females, and serum glucose and triglycerides in male chickens. Serum uric acid and NEFA linearly increased from low to high RFI in females, whereas in males, cholesterol showed the same linear response from low to high RFI. Serum alpha-1-acid glycoprotein and blood heterophil-to-lymphocyte ratio linearly increased by 35% and 68%, respectively, from low to high RFI but only in male chickens at L1. 5. Regression analysis showed significant positive relationships between RFI and serum uric acid ( R 2 = 0.49) and cholesterol ( R 2 = 0.13). 6. It was concluded that RFI-related variation in serum metabolites of chickens was largely similar for the two environments and that serum metabolite patterns could be used to predict RFI in chickens.